2010
DOI: 10.1002/hbm.20978
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of white matter tract damage in mild cognitive impairment and Alzheimer's disease

Abstract: Diffusion tensor MRI-based tractography was used to investigate white matter (WM) changes in the major limbic (i.e., fornix and cingulum) and cortico-cortical association pathways [i.e., the uncinate fasciculus, the inferior fronto-occipital fasciculus, the inferior longitudinal fasciculus (ILF), the superior longitudinal fasciculus, and the corpus callosum] in 25 Alzheimer's disease (AD) patients, 19 amnestic mild cognitive impairment (aMCI) patients, and 15 healthy controls (HC). Mean diffusivity (MD), fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
109
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 90 publications
(143 reference statements)
24
109
3
5
Order By: Relevance
“…Although the FA has been widely used as a measure to assess the integrity of brain connections (Kiuchi et al, 2009;Pievani et al, 2010;Teipel et al, 2010), we did not observe any trends toward significance in this parameter in our study.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Although the FA has been widely used as a measure to assess the integrity of brain connections (Kiuchi et al, 2009;Pievani et al, 2010;Teipel et al, 2010), we did not observe any trends toward significance in this parameter in our study.…”
Section: Discussioncontrasting
confidence: 85%
“…Hence we observed the highest trend toward significance in an increase of radial diffusivity, but no change in FA. Indeed the significant increase in radial diffusivity in the fornix in MCI and Alzheimer's disease patients compared to healthy controls found by Pievani et al (2010) may have been caused by degeneration of the cholinergic axons. In addition, significant changes in the integrity of tracts originating in the basal forebrain have been observed in Alzheimer's disease patients using tract-based spatial statistics, where measures of tract integrity were determined based on the FA parameter (Teipel et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regions of significant increase of axial D in the major corticocortical association tracts have been recently observed with normal aging 50 and in other neurodegenerative diseases, such as Alzheimer disease. 51,52 In a previous voxel-based DTI study of the same patients with ALS, 17 we found clusters of extramotor increase of MD in the frontal, temporal, and occipital lobes, which only partially overlapped the uncinate fasciculus. One explanation for this would be the different spatial resolution (tract-versus voxel-based), because the presence of microstructural damage in a small region may not have affected the average DTI metrics of the WM tract.…”
Section: Discussionmentioning
confidence: 59%
“…Suprathreshold voxels were enlarged by using TBSS fill (part of FSL) for illustrative purposes. investigations on the different diffusion parameters in normal aging, MCI, and AD 28,[74][75][76][77] provided inconsistent data with respect to the regional differences in the distribution of significant changes in FA, longitudinal diffusivity, radial diffusivity, and mean diffusivity. For example, in the above mentioned study of subjects with MCI and AD, FA was more closely related to the cognitive profile than longitudinal diffusivity or radial diffusivity.…”
Section: Dti Parameters In MCI Subtypesmentioning
confidence: 99%